Complications and failure modes of coronary embolic protection devices: Insights from the MAUDE database. Issue 2 (20th April 2021) - Megaly, Michael; Morcos, Ramez; Khalil, Charl; Garcia, Santiago; Basir, Mir; Maini, Brijeshwar; Khalili, Houman; Burke, M Nicholas; Alaswad, Khaldoon; Brilakis, Emmanouil S.
Abstract: Background: There is limited data on complications associated with the use of coronary embolic protection devices (EPDs). Methods: We queried the Manufacturer and User Facility Device Experience database between November 2010 and November 2020 for reports on coronary EPDs: Spider FX (Medtronic, Minneapolis, MN) and Filterwire EZ (Boston Scientific, Natick, MA). Results: We retrieved 119 reports on coronary EPD failure (Spider FX n = 33 and Filterwire EZ n = 86), most of which (78.2%) occurred during saphenous vein graft interventions. The most common failure mode was inability to retrieve the EPD (49.6%), with the filter trapped against stent struts in 76.2% of the cases. Other device complications included filter fracture (28.6%), failure to cross (7.6%), failure to deploy (7.6%), and failure to recapture the filter (3.4%). Filter fracture (54.5 vs. 29.1%) and failure to recapture (9.1 vs. 2.1%) were more commonly reported, while failure to deploy the filter (0 vs. 10.5%) was less commonly reported with the Spider‐FX. Conclusions: The most common modes of failure of coronary EPDs are the failure of retrieval (49.6%), followed by the filter fracture (28.6%). When using EPDs, careful attention to the technique is essential to avoid failures and subsequent complications.